Analysis of Wellhead Uplift in Offshore Thermal Recovery by Using Finite Element Numerical Simulation. (2nd January 2018) - Dong, Shexia; Zhuang, Dongsheng; Ji, Gongming; Zhu, Chunming; Sun, Ting
Abstract : Pilot test of complex thermal fluid recovery technology was conducted in NB35-2 heavy oil field. Wellhead uplift was detected among some oil wells, and development of offshore thermal recovery technology could be restricted by the serious safety problems behind. This paper is based on the specific operating conditions of one oil well in the trial block, and the simulation calculation of casing elongation and wellhead uplift are conducted by using finite element analysis. The total casing elongation calculated is 4.2 cm, which is consistent with the field test results. According to the research, we concluded that the wellhead uplift is caused by upper casing elongation. 88% of the total elongation happens in the air and seawater sections. Elongation is lesser in strata and the casing string below 360 m can be considered as anchored.